Association of vitamin D and platelet-to-lymphocyte ratio in treatment escalation risk for newly diagnosed Crohn’s disease adults - Kan Wang; Shichen Zhu; Lingya Yao; Qian Cao; Bule Shao (Nutrition Journal)
Abstract Background Accumulating research has implicated that vitamin D (VD) may be important in the pathogenesis of Crohn’s disease (CD), while the platelet-to-lymphocyte ratio (PLR) is emerging as a biomarker in immune disorders. However, the synergistic effect of VD and PLR on treatment escalation in newly diagnosed CD patients remains unclear. Therefore, this study aims to assess the interaction between PLR and VD on the subsequent use of infliximab and/or immunosuppressants in patients with CD. Methods Newly diagnosed CD patients were selected from the Sir Run Run Shaw Hospital Inflammatory Bowel Disease Biobank (SRRSH-IBC). COX proportional hazards models were employed to assess the association between VD, PLR, and treatment escalation among CD patients. Results Among 108 newly diagnosed CD adult patients, vitamin D deficiency (VDD) was prevalent (78.7%). Compared to CD patients without VDD, those with VDD exhibited a higher risk of treatment escalation, i.e., using infliximab and/or immunosuppressants (HR = 3.22, 95% CI = 1.24–8.35, P = 0.016). There is a clear trend of decreasing risk of treatment escalation as VD levels elevating (HR = 0.26, 95% CI = 0.09–0.76, P for trend = 0.014). The stratified analysis revealed a noteworthy interaction between PLR and VD levels concerning treatment escalation. Baseline VDD amplified the risk of treatment escalation among patients with elevated PLR (HR = 4.17, 95% CI = 1.51–11.53, P interaction = 0.031). Similar trends were observed when VD levels were stratified into quartiles (highest quartile vs. lowest quartile: HR = 0.18, 95% CI = 0.05–0.62, P for trend = 0.014). Conclusion This study underscores a significant interplay between VD levels and PLR in influencing treatment outcomes in CD. VDD exacerbates the risk of treatment escalation primarily in individuals with heightened PLR levels, highlighting the combined impact of vitamin D status and inflammation on disease progression of CD.